Assessing The Adaptability of Islamic Microfinance Loans to The Needs of Small Enterprises in Indonesia - Meryem Afoukane; Wiwik Utami; Lucky Nugroho (Universitas Mercu Buana, 2021)
Islamic microfinance aims to offer alternative financial products and services to the Muslim population through developing innovative microfinance services and products based on Islamic finance principles. Two main Islamic financing methods are used in Islamic microfinance: financings based on profit and loss sharing principle and financings using mark-up. The Muslim population represents more than 23% of the world population. A large part of this population is living with income below the poverty line. According to the Islamic Development Bank (2008), more than 500 million poor (with income below USD 1.25 per day) live in the five largest Muslim-majority countries (Indonesia, Bangladesh, Pakistan, Nigeria, and Egypt). Despite the enormous potential market for Islamic microfinance, Islamic Microfinance Institutions serve only 1.28 million clients, representing only 1% of the total outreach of microfinance. One possible explanation for this low outreach is that the products offered by Islamic microfinance institutions may not be well adapted to the needs of the customers. Therefore, this research aims to examine customers’ satisfaction with Islamic loans. Moreover, the study aimed to identify the loan’s selection criteria, and the areas of improvement, from the customers' perspective. This study focused on small businesses since micro-entrepreneurs have specific needs related to their businesses that differ from the other customers’ needs. The study was conducted in the context of Bank Syariah Mandiri, one of the largest Indonesian Islamic commercial banks. The study proceeded in two steps. The first step was to investigate the relevant literature on Islamic microfinance and customers’ satisfaction in the Islamic microfinance sector. The second step was collecting primary data among the customers of the micro Banking Division of Bank Syariah Mandiri. The literature review on Islamic microfinance revealed a lack of understanding of customers’ attitudes, perceptions, and preferences. Therefore, this study aimed to provide a modest contribution to the field. The survey questionnaire was used to collect primary data, and a random sampling method was used to select the participants for the survey. One hundred questionnaires were distributed to the customers who owned a micro business and had an outstanding loan balance with Bank Syariah Mandiri at the time of the survey. Descriptive and inferential statistics were used to analyze the data. The Statistical Package for Social Science (SPSS) Version 22.0 was used to generate the statistical analysis. The response rate was 100% since questionnaires were distributed to the respondents at their house or business location. The study revealed that most respondents were satisfied with the credit and its features (loan size, cost, collateral requirements, time to process the application, and application form). The credit served their business and helped them improve their sales and incomes. In addition, the study showed that the essential criteria in selecting a credit were the cost, Syariah compliance, and the process easiness. An essential finding of this study was that the religious character of the Islamic Microfinance Institution was not of great importance when selecting a microfinance institution; however, it becomes a significant concern when selecting a credit. This finding suggests the importance of enhancing Syariah compliant product innovation to increase customers’ satisfaction